2021
DOI: 10.1111/aji.13390
|View full text |Cite
|
Sign up to set email alerts
|

The role of genital mycoplasma infection in female infertility: A systematic review and meta‐analysis

Abstract: Problem: Recent studies show that lower genital tract infection with genital mycoplasma may be associated with the pathology of female infertility. However, this association remains controversial due to the variable prevalence, sample sizes, and different methods used to diagnose genital mycoplasma infection. The aim of the present meta-analysis was to gain better understanding of the specific impact of genital mycoplasma on female infertility. Method of Study:A systematic review of literature on the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 45 publications
(44 reference statements)
0
20
0
Order By: Relevance
“…Besides, our results are in line with recently reported data showing higher prevalence of M. hominis and Ureaplasma spp. urogenital infections in infertile patients, especially in women 18 , 27 29 . Furthermore, our results also showed that C. trachomatis and Ureaplasma spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, our results are in line with recently reported data showing higher prevalence of M. hominis and Ureaplasma spp. urogenital infections in infertile patients, especially in women 18 , 27 29 . Furthermore, our results also showed that C. trachomatis and Ureaplasma spp.…”
Section: Discussionmentioning
confidence: 99%
“…, who found a prevalence of U. urealyticum and M. hominis urogenital infection of 39.6% and 8.1%, respectively, in Czech women undergoing an initial infertility evaluation 34 . Interestingly, a recent meta-analysis showed a significant association between M. hominis and U. urealyticum infections and female infertility 29 . In addition, Gdoura et al .…”
Section: Discussionmentioning
confidence: 99%
“…Infertility is de ned as a multifactorial and complex reproductive system disorder in which a couple fails to establish a clinical pregnancy after 12 months of normal unprotected intercourse [1]. Biological, genetic, reproductive tract infection, lifestyle, and environmental factors are all associated with female reproductive capacity [2][3][4]. Infertility has a ected 8%-12% of couples of childbearing age globally, with the female factors accounting for nearly as much as the male factors [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…The family, Mycoplasmataceae, contains human and animal pathogens of the respiratory and genital tract that encompass the genera, Mycoplasma and Ureaplasma. The generalised term, human urogenital mycoplasma infections, encompass four species ( M. genitalium , M. hominis , U. parvum and U. urealyticum ) that are associated with symptomatic genital infections and infertility but can also be present as asymptomatic infections [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%